Nanofios de óxido de zinco e nanofitas de grafeno: fabricação, estrutura e propriedades de transporte opto-eletrônico - Leonardo Cristiano Campos (2010)
Nanomaterials such as zinc oxide nanostructures and graphene are among the most fascinating materials for device and electronic applications. Zinc oxide has proven to be an interesting material forindustrial application with properties like high optical activity in the UV energies and powerful gas sensitivity. These properties can be explored as soon we know how to produce reproducibly and in a controlled way these nanowires and their devices and to have a comprehensive understanding of how to engineer its precious properties. Graphene also holds a variety of interesting properties ranging from novel physical phenomena and various electronic applications, which can only be realized by the fabrication of nanoribbon and geometrical nanostructures. For example, ballistic room-temperature transistors, and carbon-based spintronic devices are two tantalizing possibilities which could one day be realized in a graphene nanodevices. First though, a reliable method must be found to controllably produce graphene nanostructures with specific sizes, geometries, and crystallographic edges. This thesiswill present studies about the growth of ZnO nanowires at low temperature describing a novel epitaxially induced mechanism for their growth. Futhermore, we performed a field effect transistor witha single ZnO nanowire and use, the first time, the field effect physics to produce a controllable optical device. We will show a photodetector that gating voltage controls the optical current generation and its sensitivity. Thus, just by using the gate voltage, we demonstrate that it is possible to enhance the gain of the photodetector as well as tuning its quality factor.